Visceral adipose tissue remodeling in pancreatic ductal adenocarcinoma cachexia: the role of activin A signaling - Pauline C. Xu; Mikyoung You; Seok-Yeong Yu; Yi Luan; Maya Eldani; Thomas C. Caffrey; Paul M. Grandgenett; Kelly A. O’Connell; Surendra K. Shukla; Chandramohan Kattamuri; Michael A. Hollingsworth; Pankaj K. Singh; et al. (Scientific Reports, 2022)
Abstract Pancreatic ductal adenocarcinoma (PDAC) patients display distinct phenotypes of cachexia development, with either adipose tissue loss preceding skeletal muscle wasting or loss of only adipose tissue. Activin A levels were measured in serum and analyzed in tumor specimens of both a cohort of Stage IV PDAC patients and the genetically engineered KPC mouse model. Our data revealed that serum activin A levels were significantly elevated in Stage IV PDAC patients in comparison to age-matched non-cancer patients. Little is known about the role of activin A in adipose tissue wasting in the setting of PDAC cancer cachexia. We established a correlation between elevated activin A and remodeling of visceral adipose tissue. Atrophy and fibrosis of visceral adipose tissue was examined in omental adipose tissue of Stage IV PDAC patients and gonadal adipose tissue of an orthotopic mouse model of PDAC. Remarkably, white visceral adipose tissue from both PDAC patients and mice exhibited decreased adipocyte diameter and increased fibrotic deposition. Strikingly, expression of thermogenic marker UCP1 in visceral adipose tissues of PDAC patients and mice remained unchanged. Thus, we propose that activin A signaling could be relevant to the acceleration of visceral adipose tissue wasting in PDAC-associated cachexia.